ANALISIS CAMPURAN ASPAL AC-WC PG 76 DENGAN ADDITIONAL FILLER ABU BAMBU TERHADAP STABILITAS DAN KEPADATAN ASPAL - Anggi Anggraini; Farlin Rosyad; Ely Mulyati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Roads are essential land transportation infrastructure; therefore, the quality of pavement must be maintained to ensure optimal performance and service life. One approach to improving the quality of flexible pavement in the Asphalt Concrete-Wearing Course (AC-WC) layer is by utilizing alternative materials as filler. This study investigates the effect of adding bamboo ash as an additional filler in AC-WC mixtures with PG 76 asphalt on Bulk Density and Marshall Stability. Bamboo ash contains silica (SiO₂) and exhibits pozzolanic properties that have the potential to enhance mixture performance. The bamboo ash content variations used were 0%, 0.5%, 1.0%, 1.5%, and 2.0% by total aggregate weight. Testing was conducted using the Marshall Test method in accordance with the 2018 Bina Marga General Specifications, Revision 2. The results showed that adding 1.0% bamboo ash produced the highest Bulk Density value of 2.310 g/cc, while the highest Marshall Stability value was obtained at 0.5% with 1,168.3 kg. All mixture variations achieved residual Marshall Stability values above the minimum requirement (≥90%), with the highest value of 91.47% recorded at 0.5%. Based on the balance between density and stability, the optimal bamboo ash content as an additional filler in AC-WC PG 76 is in the range of 0.5%–1.0%..Keywords: PG 76 asphalt, AC-WC, bamboo ash, filler, stability, density.